Cartography applied to the perception of spaces of rejection by students at the San Antonio Institute, Darregueira, Argentina (Huellas, 2022)
The students have a particular perception and opinion of their living space. They gain knowledge of the space through the trails they take to carry out their daily activities, such as attending educational, artistic or sports centers, and meetings with their peers or relatives, among others. Young people can classify spaces into acceptance or rejection categories depending on their experiences in the real space, the relationships they establish with other people, and their memories. This work aims at identifying the spaces of rejection perceived by the students of the San Antonio Institute in the city of Darregueira, Buenos Aires, Argentina. A survey in the student community to collect data was carried out. Afterwards, there was a statistical analysis of such data, which was presented as cartographic information. The results show that the most rejected sector of the city by young people of the community is the area located to the north of the railroad tracks. The conclusion is that students avoid spaces that generate insecurity or present deficient services and those with certain environmental contamination or those linked to a specific family situation or that implies some kind of loss.
Keywords: perception; space of rejection; students; secondary school level; cartography